2021
DOI: 10.3389/fneur.2021.735456
|View full text |Cite
|
Sign up to set email alerts
|

Small vs. Large Unruptured Cerebral Aneurysm: Concerns With the Age of Patient

Abstract: Objective: The coiling and clipping of unruptured cerebral aneurysms (UCAs) in older patients has increased rapidly, and aneurysm size was a significant factor for decision-making in the treatment of UCAs. The purpose of the study was to investigate the impact of age on the functional outcomes of patients between the small versus large UCAs.Methods: We conducted a retrospective study for consecutive cases of UCAs admitted from May 2011 to December 2020. According to the maximum diameter of UCA, patients were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Interestingly, our results show an extraordinary significance of BMI and patient age for rupture risk in our cohort. Both variables have been linked to the risk of hemorrhage in previous work [30,31], with the yet unexplained phenomenon of the obesity paradox in context of UIAs, i.e., obese patients with growing age are less likely to suffer from aneurys-mal SAH. As a consequence, BMI, age, and the aneurysm localization should have a greater weighting for the risk evaluation.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, our results show an extraordinary significance of BMI and patient age for rupture risk in our cohort. Both variables have been linked to the risk of hemorrhage in previous work [30,31], with the yet unexplained phenomenon of the obesity paradox in context of UIAs, i.e., obese patients with growing age are less likely to suffer from aneurys-mal SAH. As a consequence, BMI, age, and the aneurysm localization should have a greater weighting for the risk evaluation.…”
Section: Discussionmentioning
confidence: 98%
“…This conclusion has driven a huge growth in endovascular surgery. Since then, more and more research has focused on comparing the efficacy of intervention and surgery, and it has been found that even in the elderly, vascular intervention therapy has a lower mortality rate than microsurgery (6)(7)(8)(9)(10). However, some studies have also pointed to a higher recurrence rate of endovascular coiling compared to microsurgery (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%